2005
DOI: 10.1007/s00508-004-0288-5
|View full text |Cite
|
Sign up to set email alerts
|

Schellong test in orthostatic dysregulation: a comparison with tilt-table testing

Abstract: In conclusion the results of our study indicate that ST can be used in first line in the diagnosis of patients with orthostatic symptoms by the medical practitioner. If the ST is normal, further examination by TT is indispensable, because sensitivity of ST concerning POTS and NCS is relatively low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…A study in 67 Austrian army recruits found the standing test to have a sensitivity of 61 % and a specificity of 100 % for PoTS. 7 A sensitivity of 31 % and a specificity of 100 % for reflex syncope were noted in the same study.…”
Section: Bedside Testingsupporting
confidence: 57%
“…A study in 67 Austrian army recruits found the standing test to have a sensitivity of 61 % and a specificity of 100 % for PoTS. 7 A sensitivity of 31 % and a specificity of 100 % for reflex syncope were noted in the same study.…”
Section: Bedside Testingsupporting
confidence: 57%
“…If the blood pressure continues to fall during this period, measurements may be continued (9). The Schellong test is another method that has been used successfully to assess both OH and orthostatic dizziness (7,17,18). This test requires the subject to lay supine for 10 minutes then quickly stand up with blood pressure measurements taken at 1, 5, and 10 minutes after standing.…”
Section: Discussionmentioning
confidence: 99%
“…Fundoscopy revealed bilateral optic atrophy which had not been diagnosed before and which had not led to subjective impairments in the patient's daily life. Schellong Test [6] demonstrated a drop of systolic blood pressure by 50 mmHg in parallel to a feeling of ''fainting'' that remained uncompensated even after 10 min of standing (Fig. 1a).…”
Section: Dear Sirsmentioning
confidence: 97%